Analysis of the chemical compositions of six essential oils and evaluation of their antioxidant and antibacterial activities against some drug-resistant bacteria in aquaculture - Asmaa Chbel; Abdelhakim Elmakssoudi; Manuel Rey-Méndez; Juan L. Barja; Abdelaziz Soukri; Bouchra El khalfi (Journal of HerbMed Pharmacology, 2022)
Introduction: The extensive use of chemicals and antimicrobial agents in aquaculture has decreased the immune mechanisms of cultivated species and promoted the emergence of drug-resistant microorganisms leading to diseases among cultivated fish, affecting consumers’ health. Thus, the investigation of natural antibacterial and anti-stress agents is crucial. In the current study, we focused on the evaluation of the potential use of essential oils (EOs) as an antioxidant and antimicrobial agents in aquaculture. Methods: The EOs, obtained by hydrodistillation from clove (Syzygium aromaticum), cinnamon (Cinnamomum verum), rosemary (Rosmarinus officinalis), artemisia (Artemisia herba-alba), cedarwood (Cedrus atlantica) and oregano (Origanum compactum) were analyzed by gas chromatography/mass spectrometry (GC/MS). Their antibacterial activities were carried out against five bacteria, pathogenic to fish in aquaculture, using the well diffusion and microatmosphere methods. The pathogens used were Vibrio anguillarum, Photobacterium damselae subsp damselae, Aeromonas salmonicida, Edwardsiella tarda, and Lactococcus garvieae. Then, the minimum inhibitory and bactericidal concentrations of each EO were determined. Furthermore, the antioxidant activity was performed in vitro. Results: The investigated EOs were effective against the pathogenic strains. They showed variable constituents such as phenols, sesquiterpenes, and monoterpenes. Regarding the antioxidant activity, cinnamon, clove, and oregano EOs showed their abilities to donate hydrogen to 2,2-diphenyl-1-picrylhydrazy (DPPH) radical and scavenge free radicals produced by 2,2-azino-bis-3-ethylbenzothiazoline6-sulfonic acid (ABTS), respectively. Conclusion: These results gave insight into the potential use of phytobiotics in aquaculture as a safe strategy to substitute antibiotics to protect fish from oxidative stress and inhibit the emergence of drug-resistant bacteria for safer consumption of cultivated fish.